Monitoring rules for toxicity in Phase II oncology trials. (April 2015) - Ivanova, Anastasia; Song, Guochen; Marchenko, Olga; Moschos, Stergios
Phase I oncology trials routinely assess safety and toxicity of investigational agents and/or their combinations. However, given the relatively small number of patients usually accrued in Phase I oncology trials, the maximum tolerated dose and the recommended Phase II dose of the treatment regimen can be imprecisely defined. This may lead to testing treatment regimens in Phase II trials at doses that could lead to excessive toxicity. We review various toxicity monitoring rules that are used to stop a Phase II trial early if the probability of dose-limiting toxicity is higher than what is expected based on the Phase I assessment and provide recommendations on which rules to use.